1989
DOI: 10.1136/bjo.73.7.502
|View full text |Cite
|
Sign up to set email alerts
|

Separable evoked retinal and cortical potentials from each major visual pathway: preliminary results.

Abstract: The PERG evoked by black-and-white patterns is partly pattern specific and partly evoked by local changes in luminance. When a chequerboard reverses, the increase in brightness of part of the screen is exactly matched by decreases in other parts. It follows that the average response of many different

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
52
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 34 publications
11
52
0
1
Order By: Relevance
“…The present results are in agreement with previous published literature showing that it is possible to isolate chromatic components of the cortical response by using isoluminant gratings and the appropriate procedures to maximize chromatic response and minimize achromatic intrusion~Carden et al, 1985;Murray et al, 1987;Berninger et al, 1989;Crognale et al, 1993;Rabin et al, 1994;Kulikowski et al, 1997;Porciatti & Sartucci, 1999;Suttle & Harding, 1999;Gomes et al, 2006 Tobimatsu et al, 1995;Porciatti & Sartucci, 1999;Gomes et al, 2006! demonstrated that it is possible to evaluate color discrimination thresholds both in dichromats and normal trichromats by using transient VEP and measuring the N1 peakto-baseline amplitude, and that this procedure shows a good correlation with psychophysical measurements.…”
Section: Transient Onset/offset Vepssupporting
confidence: 93%
“…The present results are in agreement with previous published literature showing that it is possible to isolate chromatic components of the cortical response by using isoluminant gratings and the appropriate procedures to maximize chromatic response and minimize achromatic intrusion~Carden et al, 1985;Murray et al, 1987;Berninger et al, 1989;Crognale et al, 1993;Rabin et al, 1994;Kulikowski et al, 1997;Porciatti & Sartucci, 1999;Suttle & Harding, 1999;Gomes et al, 2006 Tobimatsu et al, 1995;Porciatti & Sartucci, 1999;Gomes et al, 2006! demonstrated that it is possible to evaluate color discrimination thresholds both in dichromats and normal trichromats by using transient VEP and measuring the N1 peakto-baseline amplitude, and that this procedure shows a good correlation with psychophysical measurements.…”
Section: Transient Onset/offset Vepssupporting
confidence: 93%
“…This could only be excluded by optimizing the chromatic stimulation for every individual by, for instance, the minimum-motion method [32], which is time-consuming and difficult to realize during clinical routine. Nevertheless, all BY-VEP curves showed a substantial negative peak between 110 and 220 ms, typical for isoluminant chromatic stimulation [33]. Consequently, we believe that an unimpaired application of this method in a clinical setting might only be feasible in pseudophakic patients.…”
Section: Discussionmentioning
confidence: 92%
“…More precise analyses of the PERG show that it consists of two components. PI is suggested to be partly generated by retinal ganglion cells, whereas the second negative wave N2 is associated with optic nerve activity, although both components are generated from the in ner retina [13], There is a report that PERG is produced by larger diameter retinal ganglion cells [14] which are damaged in the earlier stage of glaucoma [15], Combined abnormal ities of PI and N2 are also described in glauco matous eyes [13]. Recently, increasing atten tion has been paid to the N2 wave of glaucoma or OHT patients [16][17][18][19], It is not clear, how ever, at what stage of glaucoma or OHT the PERG abnormalities emerge.…”
Section: Introductionmentioning
confidence: 99%